Koefisien Laju Penurunan Debit Aliran Dasar Sebagai Indikator Perubahan Sistem Transfer Hujan-Aliran Suatu DAS : Studi Kasus DAS Naizin Perancis - Sunarto Goenadi (agriTECH, 1994)
The transfer of rainfall-discharge in a watershed is one of an important role in hydrological cycles. The changes of the watershed physical conditions affect significantly to that bluffer. This study focused to describe the effect of agricultural land consolidation and different area of maize on coefficient of base now recession. The experimental of the Naizin, which has an area of 1193 hectares located in France was used for the study. The result showed that the land consolidation and different area of maize cultivation affect significantly to the coefficient of base flow recession.